Conspiracy and virtue women, writing, and politics in seventeenth-century England - Wiseman, Susan (Oxford University Press, 2006)
What was the relationship between woman and politics in 17th century England? Responding to this question, this work argues that theoretical exclusion of women from the political sphere shaped their relation to it. It is a study of gender and cultural politics in the century of revolution.